ANALISIS PENERAPAN KONSEP TRIPLE BOTTOM LINE PADA USAHA AYAM POTONG BROILER “JAYSEAN FARM” DI KOTA TIAKUR KABUPATEN MALUKU BARAT DAYA - Litualy, Janet Wilsye; Kamaruddin, Sitti Fatimah; Kriswantini, Dwi (Program Studi Akuntansi PSDKU Universitas Pattimura di Kabupaten Maluku Barat Daya, 2024)
The broiler chicken business “JaySean Farm” in Tiakur City, Maluku Barat Daya Regency, is an enterprise that applies the Triple Bottom Line concept, even though it is still categorized as an MSME. This study aims to analyze the implementation of the Triple Bottom Line concept among broiler chicken businesses in Tiakur, with “JaySean Farm” as the research subject. Data collection methods include interviews and observations. The findings related to the three pillars of the Triple Bottom Line concept indicate that JaySean Farm has not fully implemented the concept in its operations. In terms of the